Correlation of Mac-2 Binding Protein Glycosylation Isomer (M2BPGi) with Liver Transient Elastography Results: An Evaluating Liver Fibrosis in Chronic Hepatitis B Patients - Haryono, Haryono; Bestari, Muhammad Begawan; Agustanti, Nenny; Girawan, Dolvy; Wahyudi, Yudi; Abdurachman, Siti Aminah; Tjandrawati, Anna (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Background: Transient elastography (TE) is widely recognized as a reliable surrogate marker for grading the severity of liver fibrosis in chronic hepatitis B (CHB) patients. Mac-2 binding protein of glycosylation isomer (M2BPGi) is a novel non-invasive serum biomarker for liver fibrosis staging in various liver diseases, including CHB. This study aimed to evaluate the correlation of M2BPGi and liver stiffness (LS), as measured through TE, in predicting the degree of liver fibrosis in CHB patients.Methods: A cross-sectional study was conducted at Dr. Hasan Sadikin General Hospital, Bandung, between September 2021 and January 2022. The study included patients diagnosed with chronic hepatitis B (CHB) based on clinical and biochemical assessments. All subjects underwent TE examination using Fibroscan®, and the M2BPGi levels were determined with an automated immunoassay analyzer HISCL-800, Sysmex, Japan. Statistical analysis was conducted using the Spearman rank correlation method, with a significance value of p0.05.Results: A total of 119 patients with chronic hepatitis B (CHB) were consecutively recruited (Male:Female = 66:53; median age: 43 years). The median M2BPGi level was 1.04 COI (range: 0.74–1.59), while the median liver stiffness (LS) was 7.3 kPa (range: 5.6–12.5). A moderate and statistically significant correlation was observed between M2BPGi and LS (r = 0.525; p 0.001). Median M2BPGi values by fibrosis stage were 0.89 COI for F0–F1, 0.88 for F2, 1.61 for F3, and 2.24 for F4 (p 0.001).Conclusion: This study revealed a moderate positive correlation between serum M2BPGi level and LS in CHB patients.